Mengembangkan Sikap Melestarikan Kearifan Lokal Siswa dengan Berkebun pada Pelajaran Projek Penguatan Profil Pelajar Pancasila - Entin Zubaedah Hasanah; Saryanto Saryanto; Rejokirono Rejokirono (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aimed to improve students' attitudes towards maintaining local wisdom through gardening activities, namely planting aloe vera as part of the Pancasila Student Profile Strengthening Project (P5). Local wisdom is a cultural asset passed down from generation to generation and is the identity of a region. Therefore, understanding and implementing local wisdom in everyday life is very important for students. The research method used in this study is qualitative with a case study approach. Data was collected by conducting direct observations of gardening activities, interviews with accompanying teachers and students, and documentation of various activities during planting and caring for aloe vera. The study found that gardening practices effectively instill local knowledge values in children. This exercise teaches students the basics of farming and helps them develop positive characteristics such as responsibility, discipline, and environmental concern. Students are accustomed to carrying out their duties according to a predetermined schedule, caring for plants with great attention, and working with friends in caring for plants.Furthermore, this exercise fosters a love of nature and increases students' knowledge of the importance of environmental conservation. This practical learning method helps students realize the importance of preserving and using local cultural activities based on local wisdom, such as gardening, which can be an excellent strategy for character development and preservation of local culture.